Improving Early Childhood Speaking Skills Through Audio Visual Media - Rambe, Khairul Fadli; Sameto, Mayang Belia; Hartini, Juli; Helena, Helena (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
Students' ability in learning speaking skills has not developed much. Many students have difficulty speaking in front of the class. They do not have high self-confidence in learning speaking skills. This problem can be overcome through audio-visual media that makes students interested in speaking by telling the contents of the learning videos they see and hear. This study aims to describe: (1). Daily learning implementation plan, Improving Learning Speaking Skills Through Audio-Visual Media for Children Aged 5-6 Years, (2). Implementation, Improving Learning Speaking Skills Through Audio-Visual Media for Children Aged 5-6 Years, (3) Assessment of Improving Learning Speaking Skills Through Audio-Visual Media for Children Aged 5-6 Years. The research conducted by the author uses a qualitative and quantitative approach with the type of classroom action research. The subjects of the research conducted by the author were 10 students. The learning process of improving learning through audio-visual media consists of 3 activities, namely: (1) Initial Activities, (2) Core Activities consisting of 3 stages, namely (a) pre-speaking stage, (2) speaking stage, (c) post-speaking stage and (3) Final Activities. To see and know the results obtained in improving speaking skills learning through audio-visual media, data related to student and teacher activities were taken. As well as data on the achievement of improving students' speaking skills learning. The results obtained after the implementation of cycles I, II and during the preliminary study have experienced good improvement.